Analisis Potensi, Efektifitas, dan Mekanisme Pemungutan Pajak Reklame terhadap Badan Pengelolaan Pajak Retribusi Daerah Kota Medan - Efrida Sari Ramayani Siahaan; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
This research journal reviews the analysis of the potential, effectiveness, and mechanism for collecting billboard taxes on the Medan City BPPRD. The purpose of this research is to find out how big the potential for advertisement tax is at BPPRD, the billboard tax collection system and also the advertisement tax levy on regional income. And how is the billing tax collection system at BPPRD. Advertising tax is one of the most important taxes as a source of local revenue. With the advertisement tax, it is hoped that it will become one of the main sources of revenue. In the case of regionally administered advertisement taxes, the potential for existing advertisement taxes is multiplied by the tax imposition market which is determined based on regional regulations. Effectiveness describes the ability of local governments to realize the advertisement tax compared to the target set based on the real potential of the region. The contribution is used to find out how big the role of the advertisement tax is to local taxes so that it can provide a clear picture of the actions and policies taken by local governments in increasing advertisement tax revenues.The type of research used is qualitative research with a naturalistic paradigm. The research instrument is direct observation and question and answer with BPPRD employees.